Survival Strategies of Muhammadiyah Schools During The Covid-19 Pandemic - Yani, Muhammad; Junjunan, Mochammad Ilyas; Hanun, Nur Ravita (School of Business, Bogor Agricultural University (SB-IPB), 2023)
The COVID-19 pandemic requires the government to issue various strategic policies that impact all sectors, especially the education sector. This research attempts to determine the strategy of private schools in Indonesia, especially in school sustainability during the COVID-19 pandemic. The interpretive paradigm with a descriptive qualitative approach was used as a study method. The location of this research was Muhammadiyah schools in Sidoarjo Regency at the junior high school level, as many as 10 schools. Data analysis was carried out using data reduction, presentation, and conclusion-drawing procedures. The results of this study indicate that Muhammadiyah junior high schools in Sidoarjo Regency use online learning as a survival strategy by utilizing the various facilities they have. In addition, several creative and innovative new programs are implemented comprehensively to support the financial limitations of schools and students. Other results also show that each location's Muhammadiyah Branch Leaders (PCM) actively support all school needs from resources, finances, and health facilities. Keywords: survival strategy, covid-19 pandemic, muhammadiyah junior high schools